MOBILE BANKING ADOPTION: THE ROLE OF PERFORMANCE AND TRUST - Sijabat, Rosdiana (Riset: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2024)
This study examines the impact of performance and trust on the acceptance of mobile banking services in Indonesia. This study employs a survey questionnaire administered to 183 individuals in Indonesia who have adopted mobile banking services. The methodology employed is Partial Least Squares Structural Equation Modelling (PLS-SEM) to assess the correlation between latent and measured variables. The research findings indicate that performance has a notable and beneficial influence on trust. Additionally, trust plays a mediating role in the connection between performance and the adoption of mobile banking. These findings highlight the significance of achieving high performance to enhance user trust and promote the acceptance of mobile banking services. Therefore, banks and financial institutions must prioritize enhancing technical efficiency and establishing and upholding consumer confidence.